Peran Dukungan Manajemen dan Tata Kelola Dalam Meningkatkan Efektivitas Audit Internal Pada Era Transformasi Digital - Rahayu Budi Susanti; Ety Meikhati; Antin Okfitasari (Jurnal Akuntansi dan Pajak, 2027)
This study aims to analyze the influence of management support and governance on internal audit effectiveness in the era of digital transformation in the regional banking sector, specifically at PT Bank Perekonomian Rakyat (BPR). The quantitative approach used a survey method with a Likert-scale questionnaire. Thirty respondents from the supervisory and managerial elements of PT Bank Perekonomian Rakyat (BPR) were selected through purposive sampling. This study employed a quantitative approach with primary data obtained through questionnaire distribution at PT Bank Perekonomian Rakyat (BPR). Data analysis was performed using SPSS with multiple linear regression analysis to determine the extent of influence of the two independent variables on the dependent variable. The results indicate that management support and governance have a positive effect on internal audit effectiveness in the era of digital transformation.